To danske konvertitbrødre fra Aalborg i begyndelsen af 1600-tallet - Helk, Vello (Kirkehistoriske Samlinger, 2005)
Two Danish convert brothersfrom Aalborg at the beginning ofthe 17. Century From Aalborg came two convert brothers: Theodor (Didrik) and Nicolaus (Niels) van Ginchel. Theodor was educated at the University of Cologne and was a Papal Scholar in Braunsberg and Vilnius 1607-10. In 1617 he entered office as a priest in the archbishopric of Salzburg. He had many problems, changed parish and had to resign 1623, because he had made a woman pregnant. In 1629 he returned and applied for office as a priest. He worked for some time as a curate, but had new problems and decided to become a Dominican. Nothing more is known of him. The second brother turned up in Rome in connection with the foundation of the S. Congregatio de Propaganda Fide 1622. In two memorials he described the current state of the Roman Catholic Church in Denmark and Norway as most deplorable, stating that immediate measures would have to be taken to remedy the situation. He put forward different proposals, among others the establishment of a special seminary for training Danish and Norwegian students who wished to or could be induced to become Catholic priests. His proposals were discussed at the sessions of the Propaganda; the final decision included an intended mission to Denmark and Norway, falling within the authority of the Apostolic Nuncio to Brussels. At the end of April 1622 the Dane was dispatched to Spain to procure the help of